Efektifitas Distribusi Dana Zakat Produktif dan Kekuatan Serta Kelemahannya Pada BAZNAS Magelang - Mufti Afif; Sapta Oktiadi (University of Darussalam Gontor, 2018)
Zakat is one of the pillars of Islam that is obligatory for Muslims and distributed to other Muslims who need it. Zakat has short and long term goals. Short-term goals are channeled to consumptive needs, namely basic household, educational and health needs. While the long-term goal, the distribution of zakat is carried out in forms of capital that can be used for economic improvement and improvement. BAZNAS Magelang has a vision and mission in distributing zakat funds to the productive zakat program. The vision and mission of BAZNAS Magelang in its distribution is to be able to change the mustahik class into muzakki. This study aims to determine the optimality of productive zakat by BAZNAS Magelang, as well as it’s strengths and weaknesses. The type of this research is descriptive qualitative, and data produced (observation), interviews (interviews) and documentation (documentaries). And to test the validity of the data in the field, researchers used triangulation techniques. The results of field studies show that the average productive zakat by BAZNAS Magelang on average has not been able to spend a large portion of their wealth to commit tithe. BAZNAS Magelang is distributed only by providing assistance to meet daily needs. BAZNAS Magelang has not exercised control, guidance, and guidance for mustahik who have received productive zakat assistance, but BAZNAS Magelang has not been able to issue assistance in the distribution of it's productive zakat assets.